Prevalence of Impulse Control Disorders among Adult Filipino Patients with Idiopathic Parkinson’s Disease seen at Jose R. Reyes Memorial Medical Center - Kristoper P. de Guzman, Jan; D. Yap, Archie; L. Go, Criscely (Journal of Neurological Research And Therapy, 2016)
Background: Impulse Control Disorders (ICDs) are characterized as pathologicalbehavioral patterns of excess impulsivity which may result as part of the non-motor complications of Parkinson’s disease (PD). These significantly affect the patient’s overall quality of life and have impact on their care givers, as well. Currently, the prevalence of ICDs among adult Filipino patients with Parkinson’s disease is unknown and less reported. Objectives: The study is intended to determine the prevalence of ICDs and its severityamong adult Filipino patients with idiopathic Parkinson’s disease seen at Jose R. Reyes Memorial Medical Center. Specifically, this study will identify risk factors and the clinical correlates to these patients. Methods: Adult Filipino patients diagnosed withidiopathic Parkinson’s diseasewhowere seen at the outpatient department from March 2015 – September 2015 are screened for the study. The Modified Hoehn and Yahr staging was utilized to determine the stage of PD. With approval from the author, the Questionnaire for Impulsive-Compulsive Disorders in Parkinson’s Disease-Rating Scale (QUIP-RS) was used for detecting the presence of ICDs and corresponding severity. Results: We were able to examine 66 patients (31 males and 35 females) withidiopathic Parkinson disease. Majority of the patients manifested with Tremor Dominant (50%) subtype, followed by Early Disease Onset (34.8%), and Non-Tremor Dominant (15.2%). Sixteen (16) out of 66 patients (24.2%) have ICD symptoms with the following incidence rates: hobbyism/ punding 56.25%, compulsive eating 50%, hypersexuality 18.75%, compulsive shopping 18.75, Dopamine dysregulation syndrome 18.75%, and gambling 12.5%. Overall average QUIP-RS score is 5.42. There is significant association of PD duration with occurrence of ICD symptoms; the longer the PD duration, the higher risk of having ICD symptoms (x2 20.41; p = 0.026). Patients with higher mean modified Hoehn and Yahr stage (2.66±0.94), t 2.735, df 64, p 0.008, have much higher incidence of ICD symptoms. Conclusion: Filipino patients with idiopathic Parkinson disease who are majority onlevodopa + carbidopa therapy may develop impluse control disorders (ICDs). Other contributory factors in development of ICDs include longer duration of PD and higher mean Modified Hoehn and Yahr stage.
Keywords: Parkinson’s disease; impulse control disorders; levodopa; dopamine agonist